PELATIHAN COPING RELIGIUS DALAM MENURUNKAN KECEMASAN PENDERITA KISTA OVARIUM - Amita, Nindy; Wahyuningsih, Hepi; Rini, Indahria Sulistya (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2021)
The research conducted by researchers aimed to determine how effective religious coping training was in reducing anxiety in patients with ovarian cysts. The hypothesis in this study is that there are differences in anxiety in the treated group. This can be seen from the pre-test, post-test, and follow-up. Thus, the treated group was more able to reduce anxiety in patients with ovarian cysts. The research design carried out by the researcher was a one-group pretest and posttest design. The scale used in the study was the SAI (State Anxiety Disorder) scale. Data analysis used the Wilcoxon test statistical technique. The results of the study proved that religious coping training was able to reduce anxiety in patients with ovarian cysts. The results showed that the pre-test and post-test sig was 0.043 and p <0.05. This result explains the difference between the pre-test and post-test scores. The changes in the participants' anxiety had given rise to changes before and after the training was given. The pre-test value with the follow-up value also has the same modifier, namely the sig value obtained is 0.043 and p <0.05. There are differences in research subjects' anxiety before being given training and after being given training given distance measurements for 2 weeks. The results of the hypothesis in this study were accepted, namely that there were differences in anxiety in the groups given treatment in this study. Keywords: Religious Coping, Anxiety, Ovarian Cysts ABSTRACT Penelitian ini bertujuan untuk mengetahui seberapa efektif pelatihan koping religius dalam menurunkan kecemasan pada pasien kista ovarium. Hipotesis dalam penelitian ini adalah ada perbedaan kecemasan pada kelompok yang diberi perlakuan. Hal itu dapat dilihat dari pre-test, post-test dan tindak lanjutnya. Dengan demikian, kelompok yang diobati lebih banyak dapat mengurangi kecemasan pada pasien dengan kista ovarium. Desain penelitian dalam penelitian ini adalah one group pretest and posttest design. Skala yang digunakan dalam penelitian adalah skala SAI (State Anxiety Disorder). Analisis data menggunakan teknik statistik uji Wilcoxon. Hasil penelitian membuktikan bahwa pelatihan koping religious mampu menurunkan kecemasan pada pasien kista ovarium. Hasil penelitian menunjukkan bahwa pre-test dan post-test sig sebesar 0,043 dan p <0,05. Ini menunjukkan bahwa ada perbedaan antara nilai pre-test dan post-test. Perubahan kecemasan peserta sendiri telah memberikan perubahan sebelum pelatihan dan setelah pelatihan diberikan. Nilai prates dengan nilai follow up juga memiliki modifikator yang sama yaitu diperoleh nilai sig sebesar 0,043 dan p <0,05. Terdapat perbedaan subjek penelitian kecemasan sebelum diberikan perlakuan dan setelah diberi perlakuan diberikan pengukuran jarak selama 2 minggu. Dengan demikian hipotesis penelitian diterima. Kata Kunci: Koping Religius, Kecemasan, Kista Ovarium